2019
DOI: 10.1136/vetreco-2018-000287
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study describing time to Salmonella seroconversion in piglets on three farrow‐to‐finish farms

Abstract: BackgroundPigs are frequently colonised with Salmonella enterica, and this constitutes a major risk for human salmonellosis. The infection can be assessed by the serological response of pigs to S enterica. A longitudinal study was undertaken on-farm to correctly describe this serological response and investigate factors associated with age at Salmonella seroconversion.MethodsThree pig farms and in each farm three successive batches were considered. Per batch, 40 piglets were selected at random from 10 sows (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…No differences were found regarding serological OD% values between infected and non-infected piglets (median OD% of 4.7 and 4.8, respectively), these values being similar to those found in piglets of the same age in other studies [ 20 ]. However, on average, OD% values were much lower than those found in the previous study on 4-wo piglets from the same farms (15.9%; [ 16 ]), evidencing the likely significant decay of maternally derived IgGs against Salmonella within the two weeks after weaning [ 7 ].…”
Section: Discussionsupporting
confidence: 83%
“…No differences were found regarding serological OD% values between infected and non-infected piglets (median OD% of 4.7 and 4.8, respectively), these values being similar to those found in piglets of the same age in other studies [ 20 ]. However, on average, OD% values were much lower than those found in the previous study on 4-wo piglets from the same farms (15.9%; [ 16 ]), evidencing the likely significant decay of maternally derived IgGs against Salmonella within the two weeks after weaning [ 7 ].…”
Section: Discussionsupporting
confidence: 83%
“…Finally, in this study, only a portion of the infected animals were seropositive after 21 days. Studies have shown that the dynamic of the animal seroconversion is variable and appears to be related to farm practices that primarily affect the time or level of exposure to the pathogen [45][46][47]. However, in the case of our study, these factors could not explain the difference in seroconversion between animals since all pigs were infected at the same time with the same dose of inoculum and were reared under the same conditions in the animal facility.…”
Section: Comparison According To the Salmonella Seropositivity Of The...contrasting
confidence: 54%
“…Similar results were obtained in a follow-up study investigating the Salmonella spp. seroconversion of piglets on three French farrow-to-finish farms (Cevallos-Almeida et al, 2019). Maternal antibodies in piglets could be detected up to ten weeks of age, and the levels measured correlated with those of the sows at the time of farrowing.…”
Section: Relevance Of Colostrum Supplymentioning
confidence: 84%